Use of isotope techniques to evaluate the recharged ability of the upper Pleistocene aquifer in the Nambo Plain - Tran , Thi Bich Lien; Nguyen , Kien Chinh; Long, Huynh; Nguyen , Van Phuc; Lam , Hoang Quoc Viet; Nguyen , Pham Tuong Minh (Nuclear Science and Technology, 2026)
In the Nambo Plain, the monitoring data on dynamics and quality of groundwater has shown declining signs in quantity and quality both in the existing groundwater aquifers, and the exploitation of groundwater in recent time is believed to be a cause of this decline. That shows the need for further research, especially on the modern recharge ability of the existing groundwater aquifers, to re-evaluate the groundwater potential of the region. For that purpose, isotope techniques are applied to evaluate the recharge ability of the upper Pleistocene aquifer, an important source of water supply in rural areas in the Nambo Plain. In this study, groundwater, river water and rainwater samples were collected and analyzed for stable isotope composition, tritium, radiocarbon and major hydro-chemical parameters. Data on stable isotope composition in groundwater are used to define the origin of groundwater while tritium and 14C content are used to determine groundwater age and to predict the aquifer’s recharge zone; and in combination with the stable isotope composition and tritium content of river water to evaluate the dynamic relationship between river water and groundwater. The obtained results show that: i) Groundwater in the study aquifer is originated from meteoric water and formed at different stages. ii) The high 3H and 14C content in some groundwater samples indicate that the aquifer has modern rainwater infiltrated as a recharge source. iii) The similarity of stable isotope composition in the Vam Co river water and groundwater adjacent to the river shows that there is a hydraulic relationship between them. This is an important basis for assessing the recharge ability to the qp3 aquifer of the Vam Co river water.